Feminist Interpretation of Fatherhood Verses in the Al-Qur’an - Muhammad Hasan Ali; Okky Octaviana; Eni Zulaiha (al-Afkar, Journal For Islamic Studies, 2025)
Gendered constructions of the father's role result in a lack of fathers' attention and care for children and domestic duties. This research is deemed urgent given the importance of fathers' roles in parenting and household activities. This study will examine verses that suggest fatherhood in depth, including its elements: emotional closeness, provision, protection, and endowment. This article presents interpretations of classical scholars considered gender-biased, then a feminist interpretation is presented as a gender-just interpretation to create equality and mutuality in childcare, furthermore allowing for the exchange of roles in household chores. The purpose of this reinterpretation is none other than to achieve the maqashid sharia, because times are always changing while the Qur'an is a guide for humans and is relevant at all times and places. This article is included in the type of qualitative research with a literature study approach. The results found that there are verses related to the concept of fatherhood that are still gender-biased, thus requiring a feminist interpretation lens as a response to create a more gender-just interpretation. With a feminist interpretation lens, fathers can spend more time with their families, both in childcare and sharing household chores with mothers (wives).